Examination of Health-Seeking Behavior in Individuals with Chronic Diseases - Coşar, Dilan Aktepe; Demirağ, Hatice; Cin, Aynur (UI Scholars Hub, 2026)
Background: Chronic illnesses are long-term, noncommunicable diseases that significantly affect daily life. In addition to physical symptoms, they can reduce quality of life by causing psychological effects such as anxiety and depression. Patients often seek health information to better manage their condition. Methods: This study aimed to examine the level of health information-seeking behavior among individuals with chronic diseases and the factors influencing this behavior. The sample group for this descriptive study consisted of 306 individuals with chronic illnesses who visited X Hospital in northeastern Türkiye between April 1, 2024, and February 1, 2025. All individuals completed a questionnaire consisting of the Patient Information Form and the Health Seeking Behavior Scale. Results: The sociodemographic characteristics of patients with chronic diseases, such as education level, marital status, and chronic disease duration, significantly affected the health-seeking behavior scores. According to the research findings, the highest mean score was determined as 12.30 ± 2.62 in the occupational health-seeking subdimension, whereas the lowest mean score was determined as 8.78 ± 3.83 (min – max: 3 – 15) in the traditional health-seeking subdimension. The total mean score of the Health Seeking Behavior Scale was 32.2 7± 7.73. Conclusions: Individuals with chronic illnesses tend to prefer professional health care services when seeking health-related behaviors. Health-seeking behaviors were higher among high school graduates, single individuals, and those without chronic illnesses.